(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Tumour cachexia represents the most severe form of malnutrition in cancer patients and is responsible for nearly one-third of cancer-related deaths, either directly or indirectly. Malnutrition in cancer patients arises from factors related to the tumour itself, the patient’s condition, or the treatment received. Methods: This study reviews the primary mechanisms contributing to malnutrition in cancer patients, particularly in the context of different treatment modalities such as chemotherapy, radiation therapy, and surgery. The physiological impact of malnutrition, its implications on patient outcomes, and associated healthcare costs are also examined. Results: Malnutrition in cancer patients occurs through four essential pathways: • Inadequate nutrition and energy consumption – due to reduced appetite or difficulty in eating. • Modifications to nutrient absorption and digestion – caused by tumour-related metabolic alterations. • Increased nutritional requirements – resulting from the body’s inflammatory response to cancer. • Changes in nutrient metabolism – leading to muscle wasting and weight loss. The consequences of malnutrition include loss of muscle mass and strength, reduced functional status, impaired quality of life, and greater dependence on caregivers. It also hampers the body’s natural healing processes, increasing the risk of surgical complications such as infections and wound dehiscence. Additionally, malnutrition contributes to prolonged hospital stays, raising overall treatment costs. Severe weight loss is strongly correlated with lower survival rates in cancer patients. Conclusion: Malnutrition is a critical concern in cancer care, significantly impacting patient health, treatment outcomes, and healthcare expenditures. Early intervention and nutritional support strategies are essential to mitigate its effects and improve patient prognosis.